Pashechko M., Berezhanskyi T. Improving resource recovery operation and methods elements fire equipment protective coatings eutectic - Пашечко, М. І.; Бережанський, Т. Г. (Problems of Tribology, 2018)
To perform the tasks in order to rescue people and valuables DSNS rescuers used a variety of equipment and special tools, the reliability of which depends not only the lives of victims, but also of rescuers. Today, the fire and rescue units Ukraine frequently used equipment, which came lifetime or the lifetime of parts and working bodies which are partly worn. The use of protective coatings based on eutectic alloy Fe-Mn-CB-Si alloy Cr can increase the wear resistance of the fire and rescue equipment, as well as application of these materials by welding GMA (MAG) recovers partially worn, or damaged operating elements and details, is more economically advantageous than the replacement of parts with new ones. When surfacing sheeting tightly adjoins and forms a tight bond with the substrate material without significant defects and delaminations